Interactive effects of temperature and food availability on the growth of Arctica islandica (Bivalvia) juveniles. (February 2018) - Ballesta-Artero, Irene; Janssen, Reneé; van der Meer, Jaap; Witbaard, Rob
Abstract: The interest in Arctica islandica growth biology has recently increased due to the widespread use of its shell as a bioarchive. Although temperature and food availability are considered key factors in its growth, their combined influence has not been studied so far under laboratory conditions. We tested the interactive effect of temperature and food availability on the shell and tissue growth of A. islandica juveniles (9–15 mm in height) in a multi-factorial experiment with four food levels (no food, low, medium, and high) and three different temperatures (3, 8, 13 °C). Shell and tissue growth were observed in all treatments, with significant differences occurring only among food levels (2-way ANOVA; P-value < 0.05). Siphon activity (% open siphons), however, was affected by temperature, food, and the interaction between them (2-way ANOVA; P-value < 0.05). Siphon observations, as indication of feeding activities, played a key role to better understand the growth variation between individuals. Highlights: Between 3 and 13 °C, only food level significantly affected shell and tissue grown of the bivalve Arctica islandica. A. islandica siphon activity responds to combined effects of algal concentration and temperature. Very low and very high algal concentrations led to shell closure and reduction of filtration rate on A. islandica . Siphon activity can be used as a predictor of shell growth.